Natural variability of essential oil and antioxidants in the medicinal plant Turnera diffusa - Urbizu González, Ana Lucía; Castillo Ruiz, Octelina; Martínez Ávila, Guillermo Cristian Guadalupe; Torres Castillo, Jorge Ariel (2017)
Objective: To evaluate differences in yield and composition of the essential oil and antioxidant contents in Turnera diffusa plants from localities in central region of Tamaulipas. Methods: Samples were collected in Tamaulipas, Mexico in the arid zone. Essential oil was obtained through steam distillation and analyzed using GC–MS. Polyphenol contents, antioxidant activities using ABTS and ferric reducing antioxidant power (FRAP) methods also were evaluated